2020
DOI: 10.1101/2020.08.27.269225
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Crucial Role ofSalmonellaGenomic Island 1 Master Activator in Parasitism of IncC plasmids

Abstract: IncC conjugative plasmids and the multiple variants of Salmonella Genomic Island 1 (SGI1) are two functionally interacting families of mobile genetic elements commonly associated with multidrug resistance in Gammaproteobacteria. SGI1 and its siblings are specifically mobilised in trans by IncC conjugative plasmids. Conjugative transfer of IncC plasmids is activated by the plasmid-encoded master activator AcaCD. SGI1 carries five AcaCD-responsive promoters that drive the expression of genes involved in its exci… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 68 publications
3
9
0
Order By: Relevance
“…SGI1‐family elements are sophisticated parasites of IncA and IncC plasmids as they do not simply utilize the plasmid‐encoded T4SS but exploit the control mechanisms of the helper plasmid for timing of their excision and plasmid‐like replication (Kiss et al., 2015; Szabó et al., 2021). They modify the T4SS for their own benefit (Carraro et al., 2017) and destabilize the helper (Durand et al, 2021b; Harmer et al., 2016; Szabó et al., 2021), possibly in order to ensure the stable vertical transfer. These interventions increase the efficiency of SGI1 transfer and the stability of the island in the host bacteria when coexisting with the helper plasmid.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…SGI1‐family elements are sophisticated parasites of IncA and IncC plasmids as they do not simply utilize the plasmid‐encoded T4SS but exploit the control mechanisms of the helper plasmid for timing of their excision and plasmid‐like replication (Kiss et al., 2015; Szabó et al., 2021). They modify the T4SS for their own benefit (Carraro et al., 2017) and destabilize the helper (Durand et al, 2021b; Harmer et al., 2016; Szabó et al., 2021), possibly in order to ensure the stable vertical transfer. These interventions increase the efficiency of SGI1 transfer and the stability of the island in the host bacteria when coexisting with the helper plasmid.…”
Section: Discussionmentioning
confidence: 99%
“…SGI1 encodes an FlhDC‐family activator and three T4SS components that are related to and can substitute their helper‐encoded homologues. These SGI1 derived proteins have important roles in the parasitism of SGI1 on the helper plasmid (Carraro et al., 2017; Durand et al, 2021b).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, IncC plasmids and SGI1 share a complex transcriptional regulatory network, each element having homologous master activators, i.e. AcaDC and SgaDC, respectively, which have been shown to activate the same regulons in both elements (15, 18, 19, 21). Durand et al recently demonstrated that SgaDC and AcaDC activate the expression of AcaB, an IncC transcriptional regulator which in turn in cooperation with AcaDC have been shown to trigger the expression of the conjugative IncC machinery through a positive feedback loop of mutual expression (18, 24).…”
Section: Introductionmentioning
confidence: 99%